2010
DOI: 10.3109/00952990.2010.503823
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Addictions

Abstract: The phenomenology of excessive nonparaphilic sexual disorder favors its conceptualization as an addictive behavior, rather than an obsessive-compulsive, or an impulse control disorder. Moreover, the criteria that are quite close to those of addictive disorders were recently proposed for the future DSM-V in order to improve the characterization of this condition. Finally, controlled studies are warranted in order to establish clear guidelines for treatment of sexual addiction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
97
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(105 citation statements)
references
References 36 publications
2
97
0
6
Order By: Relevance
“…addictive (Widyanto & Griffiths, 2006;Young, 2004), pathological (Davis, 2001), or problematic (Caplan, 2002) Internet use. Based upon similarities with other behavioral and substance addictions (Block, 2008;Garcia & Thibaut, 2010;Grant, Brewer & Potenza, 2006;Potenza, 2006Potenza, , 2008, Internet use disorder will be included in the appendix of DSM-V (Holden, 2010), which emphasizes the clinical relevance and the lack of empirical evidence on this topic, so far.…”
Section: Introductionmentioning
confidence: 99%
“…addictive (Widyanto & Griffiths, 2006;Young, 2004), pathological (Davis, 2001), or problematic (Caplan, 2002) Internet use. Based upon similarities with other behavioral and substance addictions (Block, 2008;Garcia & Thibaut, 2010;Grant, Brewer & Potenza, 2006;Potenza, 2006Potenza, , 2008, Internet use disorder will be included in the appendix of DSM-V (Holden, 2010), which emphasizes the clinical relevance and the lack of empirical evidence on this topic, so far.…”
Section: Introductionmentioning
confidence: 99%
“…The literature offers various conceptual isations of excessive nonparaphilic sexual disorder based on the models of obsessive-compulsive disorder, impulse control disorder, outofcontrol excessive sexual disorder, and addictive disorder (Garcia 2010). However, studies suggest that, if internet sex addiction does exist, it is not a standalone disorder, but a behaviour arising in association with several other psychiatric disorders.…”
Section: A Stand-alone Disorder?mentioning
confidence: 99%
“…It has been suggested that, like chemical addictions, sex addictions consist of: experiencing a recurrent failure to resist impulses to engage in a specific sexual behavior, an increased sense of tension immediately prior to initiating the sexual behavior, and pleasure or relief at the time of engaging in the sexual behavior (Garcia & Thibaut,201 0). Like chemical addictions, sex addiction also includes an escalation of sexual behaviors as the disorder progresses, withdrawal symptoms such as depression, anxiety, and guilt related to a reduction of sexual activities, as well as difficulty stopping or reducing the frequency of sexual behaviors (Garcia & Thibaut, 2010).…”
mentioning
confidence: 99%
“…Garcia & Thibaut (2010) argue that sex addiction is an impulse control disorder or an obsessive compulsive disorder. Sex addiction has been labeled as an impulse control disorder due to the fact that one often fails to resist the drive, impulse, or temptation to act out the behavior that may be harmful to oneself or others.…”
mentioning
confidence: 99%
See 1 more Smart Citation